The Effect of Digital Literacy and Future Time Perspective on The Self-Confidence of Prospective Vocational School Graduates Entering the Job Market - Prianto, Agus; Winardi, Winardi; Qomariyah, Umi Nur (Technium Social Sciences Journal, 2021)
We are now living in digital age. Almost all activities are carried out using digital technology devices. Various information and knowledge are saved in digital devices. Therefore, anyone who lives in the present and the future should have adequate digital literacy. This study aims to determine the level of digital literacy, future time perspective, and the self-confidence of prospective vocational school graduates in entering the job market. In addition, this study also intends to answer whether there is an influence of digital literacy and future time perspective on the self-confidence of prospective vocational school graduates entering the job market. This research revealed that the digital literacy level of prospective vocational school graduates is at a moderate level, the future time perspective is at a good level, and the level of self-confidence entering the job market is at a good level. Mediated by a future time perspective, digital literacy indirectly affects the self-confidence of prospective vocational school graduates in entering the job market. There is no significant relationship between digital literacy and confidence in entering the job market. Thus, digital literacy–future time perspective–self-confidence in entering the job market is a pathway used to prepare prospective vocational school graduates to enter the job market. Vocational schools are directed to develop real programs to increase students’ digital literacy to encourage the growth of self-confidence of prospective vocational school graduates in entering the job market.